Effects of qigong exercise on cardiovascular risk factors in patients with metabolic syndrome: A systematic review and meta-analysis - Tao, Shuoxiu; Li, Zaimin (Frontiers in Physiology, 2023)
Background: There is no articles have systematically evaluated the effects of Qigong exercise on cardiovascular risk factors in patients with metabolic syndrome(MetS). Therefore, this systematic review aimed to evaluate the effects of Qigong exercise on cardiovascular risk factors in patients with MetS. Objective: Relevant randomized controlled trials (RCTs) were identified to conduct a meta-analysis of the effects of Qigong exercise on patients with MetS, and to further explore the overall impact, heterogeneity, and publication bias related to the effects of Qigong exercise on MetS. Methods: Pubmed, Web of Science, The Cochrane Library, Scopus, Embase, Physiotherapy Evidenced Database, Google Scholar, Chinese Biomedical Literature Database, Chinese National Knowledge Infrastructure Database, Chinese Science, Wanfang Data, and the VIP database were used to search. The search duration was set from the establishment of the database to April 16, 2022. We used the “Bias Risk Assessment” tool recommended by Cochrane Manual 5.0 to assess the methodological quality of the included literature and the R (version 3.6.2) package gemtc to analyze the data. Results: A total of seven RCTs with 486 participants were included in the meta-analysis. The results showed that Qigong exercise had significant effects on WC(standardized mean difference[SMD]= -0.67; 95% CI, -1.16 to -0.17), SBP(SMD = -0.53; 95% CI, -0.78 to -0.28) and TG level(SMD = -0.60; 95% CI, -0.79 to -0.41). Subgroup analyses showed that 6-month Qigong exercise significantly improved DBP(SMD = -1.06; 95% CI, -1.57 to -0.56), HDL-C level(SMD = 1.45; 95% CI, 1.06 to 1.85), TC level(SMD = -0.65; 95% CI, -1.04 to -0.27), and BMI(SMD = -0.97; 95% CI, -1.23 to -0.72). For FBG(SMD = -1.12; 95% CI, -1.58 to -0.67), the effect of a 3-month intervention seemed more effective than 6 months of Qigong exercise, but the evidence was insufficient. In addition, Qigong exercise had minimal effects on LDL-C levels(SMD = -1.22; 95% CI, -1.95 to -0.50). Conclusion: Qigong may be an alternative exercise mode to improve cardiovascular risk factors in patients with MetS. However, the findings are limited by the number and quality of the included studies, and require validation through more high-quality studies.